Level and Noise Sources in the Neonatal Intensive Care Unit of a Reference Hospital - Alma Damaris Hernández-Salazar; Josefina Gallegos-Martínez; Jaime Reyes-Hernández (Universidad de Antioquia, 2020)
Objective. Determine the level of environmental and periauricular noise in preterm babies and identify the sources generating noise in the Neonatal Intensive Care Unit -NICU- of a reference hospital in San Luis Potosí, Mexico. Methods. Cross-sectional and analytic study of the measurement of the level of environmental noise in five critical areas of the NICU, according with the method of measurement of noise from fixed sources by the Mexican Official Norm and periauricular at 20 cm from the preterm patient's pinna. The measurements were carried out during three representative days of a week, morning, evening and nocturnal shifts. A STEREN 400 sound level meter was used with 30 to 130 dB range of measurement and a rate of 0.5 s. Results. The average level of periauricular noise (64.5±1.91dB) was higher than the environmental noise (63.3±1.74 dB) during the days and shifts evaluated. The principal noise sources were activities carried out by the staff, like the nursing change of shift and conversations by the staff, which raised the level continuously or intermittently, operation of vital support equipment (alarms) and incidences (clashing of baby bottles and moving furnishings) produced sudden rises of noise. Conclusions. Environmental and periauricular noise in NICU exceeds by two and almost three times the 45 dB during the day and 35 dB at night from the norm in hospitals. It is necessary to implement permanent noise reduction programs to prevent sequelae in the preterm infant and professional burnout in the nursing staff.